(untitled) (Revista Contexto & Saúde, 2022)
Diabetes Mellitus is a public health problem that causes numerous hospitalizations. This study evaluated adherence to drug treatment of diabetic patients registered in the Hiperdia program at a health unit in the municipality of Jequié-Ba. This is a quantitative, descriptive analytical and cross-sectional study, which was developed at the Almerinda Lomanto Health Center and involved 81 patients. A form referring to sociodemographic aspects, lifestyle and clinical aspects of the disease was applied, in addition to the Morisky and Batalla tests, which assessed adherence to drug treatment. Data analysis was performed using the SPSS program. The association between adherence and independent variables was analyzed using the chi-square test (X2), the association hypothesis was accepted when the probability was ≤ 0.05. The sociodemographic profile showed the highest prevalence of women, elderly, single, retired, with incomplete elementary education and income of 1-2 minimum wages. Adherence was observed in 40.7% of participants, using the Batalla test, and 51.9% using the Morisky test. As for the statistical association, adherence by the Morisky test was significant when related to income, however, by the Batalla test, only the smoking variable was significant. There was no significant association between the other variables in both tests. Patients seen at the Health Center reported difficulty in adhering to medication therapy for diabetes, mainly due to the lack of information about the disease and treatment, emphasizing the importance of patients’ communication with health professionals.